Interpreting Collocations in the Holy Quran: A Ricoeurian Hermeneutic Study of Five Product Translation Interpretations - Ali Mohammed Saleh Al-Hamzi (LPPM Universitas Advent Indonesia, 2026)
The Quran is a significant religious text for millions of people worldwide, and its interpretation is of great importance to scholars and researchers in the field of Islamic studies. One area of interest in the Quranic text is the use of collocations, such as